PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI KABUPATEN PELALAWAN - Mohamad Suparno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low results of social studies class V SD Negeri 010 Silikuan Hulu Kecamatan Ukui. This is evidenced by of 26 students only 11 (41.67%), which reached KKM, to research the learning improvement by implementing cooperative learning model Jigsaw. This research is a class act who do as much as two cycles. The collection of data in research adalag with the testing techniques. The study states that the implementation of cooperative learning model jigsaw can improve learning outcomes IPS, it is seen from: the average student learning outcomes which increased 20.25% from the average value of the basic score is 69.58 into 83.67 at UH the first cycle, and the average value UH second cycle increased 31.50% from the average score of 69.58 into 91.50 basis. The percentage of classical completeness achievement has been as expected. Which, on the basis of completeness klasikalnya score is 41.67% with the category is not exhaustive and the UH first cycle increased to 87.50% with the category completely, then at UH second cycle increased to 91.67% with the category completely.